GAMBARAN HITUNG LEUKOSIT PRE OPERATIF PADA TIAP-TIAP TINGKAT KEPARAHAN APENDISITIS AKUT ANAK (BERDASARKAN KLASIFIKASI CLOUD) DI RSUD ARIFIN ACHMAD PROVINSI RIAU PERIODE JANUARI 2011-DESEMBER 2012 - Pratiwi, Suci; Arbi, Inzta; Lestari, Siti Mona Amelia (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Pediatric acute appendicitis is surgical case which one of diagnosis component islaboratory test. The leukocyte count is one of the most common laboratory tests usedbecause leukocyte count increased approximately 70% in children with acuteappendicitis. Acute appendicitis in pediatric is based on Cloud Classification consistsof simple, suppurative, gangrene, abscess and perforation. The aim of this study wasinvestigate pre operative white blood count toward diagnosis of acute appendicitis inpediactric based on Cloud Classification. This retrospective descriptive study wasdone since February 2014. About 75 patients were include in this study. Data wereobtained from medical record at Department of Surgical RSUD Arifin AchmadPeriod January 2011-December 2012. It was found that the largest age group 13-18year (78,7%). The number of men and women was relatively equal. A total of 61,3%of children had leukocytosis and leukocyte count mean value increases with theseverity of appendicitis, there were simple 12.500/mm3, suppurative 14.000/mm3,gangrene 15.800/mm3, abscess 17.400/mm3 and perforation 22.000/mm3. Theconclusion of this study was an increase in leukocytes at each level of appendicitisbased on Cloud Classification.Key words: pediatric acute appendicitis, leukocyte count, Cloud Classification